Determinants of Stock Price in Nepalese Market (The International Research Journal of Management Science, 2018)
The aim of this study is to determine the relationship between stock price and explanatory variables like: DPS, EPS, P-E ratio, BV, Market to BV for the period 2012 to 2017. Using simple and multiple regression analysis and descriptive statistics this study investigates the factor affecting the stock price. With the sample size of 11 financial and nonfinancial firms of Nepal, the result indicates that the variables Market to BV, P-E ratio are the significant determinants of stock price which directly affect the stock price. Likewise, DPS, BV also have significance positive influence on stock price whereas EPS has minimum influence on the stock price.